Role of safe sites in black spruce recruitment and growth release in post-fire Kalmia heath - Kravchenko, Dmitri (2012)
The goal of this thesis was to explain black spruce regeneration in postfire sheep laurel (Kalmia angustifolia L., hereafter referred to as Kalmia) dominated chronosequence in light of safe site density. The concept of safe site was expanded by including germination as well as seedling establishment and growth phases. Proliferation of Kalmia, which dominates heathlands of eastern Newfoundland, has been reported to severely restrict conifer recruitment and growth. As a result, forest regeneration in Kalmia heath can be delayed by as much as 60 years. Despite numerous studies, the process by which colonization and establishment of black spruce occurs in Kalmia heath is poorly understood. This problem is addressed in two chapters. In chapter one, it was hypothesized that post-fire black spruce stem density, which represents a relative measure of safe site abundance per plot, is a function of variation in microsite conditions, rather than time since fire. The second hypothesis was that the partially safe sites defined by seedling establishment, but poor seedling growth, overtime, become safe sites allowing a growth release. In chapter two, it was hypothesized that microsites created by scarification and microsite mulching (MSM) enhance black spruce growth by removing the inhibitory effects of Kalmia and its organic matter by increased decomposition and soil moisture. The main findings of the research are (1) black spruce safe site density in post-fire sites is low and diminishes over time; (2) relative safe site density is negatively associated with organic matter thickness; (3) most of the recruited black spruce experience a period of stunted growth; (4) with time, stunted black spruce may overcome the growth check; (5) the likelihood of the growth release has an inverse relationship with OM thickness and positive relationship with OM decomposition; (6) young black spruce seedlings planted in artificially created safe sites show significantly higher growth rates compared to those in undisturbed heath. Based on these results, it was concluded that i) safe sites play a critical role in colonization and growth of black spruce, ii) high OM depth (> 5 cm) makes a microsite unsafe for black spruce regeneration, and iii) safe sites created by scarification and microsite mulching (MSM) can enhance black spruce regeneration in Kalmia health. By examining the problems of black spruce forest regeneration in Kalmia dominated sites, this study advances the current understanding of the safe site concept and its application in forest restoration. From the conceptual point of view, it revealed the need for extending the safe site concept beyond the germination stage to include seedling and adult life stages. This research demonstrates that by removing the growth limiting conditions, it is possible to create safe sites by scarification and MSM which enhance conifer growth in habitats that are otherwise unsuitable for conifer regeneration. For national parks and other conservation areas MSM is preferred to scarification for its minimum soil disturbance.